TEKNOLOGI FERMENTASI BEBERAPA TUMBUHAN SUMBER HORMON TERHADAP PERUBAHAN PROFIT TERNAK AYAM BROILER (Gallus domesticus). - Meriksa Sembiring,; Alfath Rusdhi, (Journal of Innovation Research and Knowledge, 2025)
The purpose of this study was to determine the effect of plant hormones on profit in raising broiler chickens (Gallus domesticus). And to determine the cost efficiency in the use of different plant hormones for broiler livestock (Gallus domesticus). The experimental design used in this study was a non-factorial Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments tested were: Ho (control) without hormones, H1 (Neobro), H2 (banana tubers), H3 (bean sprouts), H4 (sweet potato shoots). Hormone testing was taken from plants by adding EM4 bioactivator and molasses which were fermented for 1 week except for hormones from bean sprouts. The three fermentation results were complete and could be used as a mixture in daily drinks. The parameters observed were production costs, Total Revenue, profit/loss analysis, R/C ratio analysis, Income Over Feed Cost (IOFC). From the results of the research that has been analyzed, it was found that the use of hormones from several plant hormones was seen Production costs showed no significant difference, R/C analysis was significantly different and Total revenue, total profit and loss and IOFC were very significantly different. The best plant hormones in obtaining higher profits were from banana stems (H2) and sweet potato shoots (H4) with the lowest parameters in the control (H0)